Наративізація сакрального в поемі Тараса Шевченка “Марія” - Брайко, О. (Слово і Час, 2008)
У статті аналізуються знаково-символічні структури твору. З’ясовується художнє навантаження розповіді, ціннісні контексти автора й персонажів, семантика мікрообразів, хронотоп поеми, структура сюжету, особливості взаємодії євангельської фабули й новочасного художнього мислення. Залучаються концепти структуральної поетики, міфопоетики, культурний інтертекст, фольклорні джерела стильової манери поета. Увиразнюються елементи раціоналістичного конструювання образів і дії. Твір Т.Шевченка розглядається як взірцева модель людського існування, водночас сугестивна й автосугестивна. This article provides the analysis of semiotic and symbolic structures of the poem. The author of the essay elucidates the artistic nature of the narration, outlines the system of values characteristic of the writer and of his characters, sketches out the semantics of the figurative details, investigates the chronotopos of the poem, the structure of its plot and the peculiarity of interrelations between the evangelic story and the literary consciousness of the Romanticism. The present analysis involves some notions of structural poetics and mythopoetics, cultural intertext and the folkloric sources of the poet’s style. The author accentuates the rationalistic construction of the poem’s imagery and plot. T.Shevchenko’s poetic work is stated to be a perfect model of human existence, suggestive and autosuggestive at once. В статье анализируются знаково-символические структуры произведения. Освещается художественная нагрузка повествования, ценностные контексты автора и персонажей, семантика микрообразов, хронотоп поэмы, особенности взаимодействия евангельской фабулы и романтического художественного мышления. Привлекаются концепты структуральной поэтики, мифопоэтики, культурный интертекст, фольклорные источники стилевой манеры поэта. Интерпретируются элементы рационалистического конструирования образов и действия. Поэма Т.Шевченко рассматривается как образцовая модель человеческого существования, одновременно суггестивная и автосуггестивная.